Essential healthcare services during the COVID-19 pandemic: a cross-sectional study of community needs and perspectives in West Java, Indonesia - Emma Fletcher; Aufia Espressivo; Gita Kusnadi; Nisaatul Maharanita Fitrianingrum; Muhammad Anugrah Saputra; Nabilla Sophiarany; Febriansyah Soebagio (BMJ Open, 2024)
Objectives While issues in healthcare facilities during the COVID-19 pandemic have been widely discussed, little is known about health service issues from community (demand) sides. This study aimed to identify community needs in the utilisation of health services and highlight the key roles and barriers that community health workers (CHWs) face in delivering community-based services during the pandemic.Design Cross-sectional study.Setting 38 randomly selected villages covered by 21 preidentified community health centres in 3 districts in West Java, Indonesia. The survey was conducted from 22 January 2022 to 7 February 2022 (2 years after the pandemic began).Participants 118 respondents, consisting of community leaders, vulnerable group representatives and CHWs.Results Laboratory examination (55.1%), emergency care (52.5%), non-communicable disease screening (50%) and routine treatment (49.2%) were perceived as the highest unmet needs of essential healthcare services. Fear of infection (90.3%) became one main barrier to access healthcare services. Vulnerable populations including lower socioeconomic groups (61.2%), households with elderly (25.4%), persons with disabilities (25.4%), pregnant women, people with mental illness and people with lower education (26.9%) were reported facing difficulties in accessing healthcare services. Further, the pandemic was deemed to have significantly impacted the community economic situation (91.5%). CHWs were actively engaged in community-based services and were mentioned as the first contact when the community needed help (57.6%). CHWs reported essential needs on financial support (45.2%), logistics (54.8%) and protective equipment (22.6%).Conclusions Essential health services for the community, including those belonging to vulnerable groups, were highly impacted during the pandemic. CHWs appear to have significant roles in delivering health services during this health crisis, hence, adequate support is needed to equip them in strengthening pandemic response.